2023
DOI: 10.1007/s00338-023-02433-0
|View full text |Cite
|
Sign up to set email alerts
|

Movement dynamics, sediment turnover and sheltering behaviours of the nocturnal coral reef sea cucumber, Stichopus cf. monotuberculatus

Benjamin C. T. Gray,
Maria Byrne,
Matthew Clements
et al.

Abstract: Animal movement and feeding studies shed light on ecological roles and can inform management strategies for fished species. However, the feeding and movement of nocturnal sea cucumbers have been rarely studied. We determined the movement dynamics, feeding ecology and sheltering behaviour of the nocturnal Stichopus cf. monotuberculatus (dragonfish) at One Tree Reef and Heron Island Reef on the southern Great Barrier Reef. The short-term movement of individual sea cucumbers were tracked, and sediment defecation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Fishermen and the community rarely take this type of sea cucumber so that its existence is easily found and very abundant compared to the type of sea cucumber that has high economic value. The people of the Kepulauan Seribu National Park search for sea cucumbers with a time ratio of every day, the search is carried out every day at the start of the evening, because they believe that it is easier to find sea cucumbers at night, this fact is reinforced by research that sea cucumbers are nocturnal animals (Purcell et al 2023), in addition to their nocturnal nature, sea cucumbers can also be found in the light of day, but the percentage is small and tends to be difficult, because sea cucumbers take refuge in coral reef ecosystems (Purcell et al 2023) in (Gray et al 2023). Remote locations in Indonesia have been used as used as fishing grounds because cucumber because cucumber fishermen have to scour the places to find the target species that the market wants.…”
Section: Identification Of Sea Cucumbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishermen and the community rarely take this type of sea cucumber so that its existence is easily found and very abundant compared to the type of sea cucumber that has high economic value. The people of the Kepulauan Seribu National Park search for sea cucumbers with a time ratio of every day, the search is carried out every day at the start of the evening, because they believe that it is easier to find sea cucumbers at night, this fact is reinforced by research that sea cucumbers are nocturnal animals (Purcell et al 2023), in addition to their nocturnal nature, sea cucumbers can also be found in the light of day, but the percentage is small and tends to be difficult, because sea cucumbers take refuge in coral reef ecosystems (Purcell et al 2023) in (Gray et al 2023). Remote locations in Indonesia have been used as used as fishing grounds because cucumber because cucumber fishermen have to scour the places to find the target species that the market wants.…”
Section: Identification Of Sea Cucumbersmentioning
confidence: 99%
“…Because they believe that sea cucumbers are more easily found at night, this is supported by research that shows sea cucumbers are nocturnal animals (Purcell et al 2023). Although sea cucumbers can also be found during the day, the percentage is small and they tend to be difficult to find because they hide in coral reef ecosystems (Purcell et al 2023) according to (Gray et al 2023). Many fishermen prefer to catch sea cucumbers with high economic value.…”
Section: Spatial Distribution Of Sea Cucumber Density and Type Of Hab...mentioning
confidence: 99%